THE EFFORTS TO IMPROVE THE QUALITY OF PASSPORT PROCESSING SERVICES IN KANTOR IMIGRASI KELAS 1 TPI SEMARANG - Amin, Muhammad Al; Priyadi, Budi Puspo; Sulandari, Susi; D, Ida Hayu (Journal of Public Policy and Management Review, 2021)
Passport making service is a form of public service under the Ministry of Law and Human Rights. As a state organizing apparatus in charge of serving citizens in the best possible way, the Ministry of Law and Human Rights of the Republic of Indonesia is considered the implementation of its duties by the Directorate General of Immigration. Immigration is the only vertical agency that takes care of the arrival and return of Indonesian citizens and foreign nationals to be able to enter and exit Indonesian territory. A passport is a cross- border travel document that is a valid condition of departure or return of a citizen to enter or exit Indonesia. Results and discussions. The quality of passport-making services at The Immigration Office class I TPI Semarang as a big good with new innovations to improve its quality, namely with immigration authorities socializing about immigration in 5 districts 2 cities in the area of the immigration office class 1 TPI Semarang, the incandration of integrity zones to achieve the predicate of corruption-free areas in 2019, ambassadors of services, and innovations of Jempol Semar made to serve people disabilities or special diseases. The conclusion and advice on the quality of passport management services at TPI Semarang Class I Immigration Office should be improved by increasing the amount of human resources (HR) for people with disabilities or special illnesses, expanding parking lots and increasing photo space for people with disabilities so as not to join the waiting room.